2020
DOI: 10.1016/j.watres.2019.115281
|View full text |Cite
|
Sign up to set email alerts
|

Predatory bacteria in combination with solar disinfection and solar photocatalysis for the treatment of rainwater

Abstract: The predatory bacterium, Bdellovibrio bacteriovorus, was applied as a biological pre-treatment to solar disinfection and solar photocatalytic disinfection for rainwater treatment. The photocatalyst used was immobilised titanium-dioxide reduced graphene oxide. The pre-treatment followed by solar photocatalysis for 120 min under natural sunlight reduced the viable counts of Klebsiella pneumoniae from 2.00 × 10 9 colony forming units (CFU)/mL to below the detection limit (BDL) (<1 CFU/100 µL). Correspondingly, et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Post-treatment filtration is still required to separate the photocatalyst from the solution, and cost/energy analysis also needs to be performed to examine if the additional complexity and input energy are worth the increased efficiency. To remove the need for filtration, the photocatalyst can be immobilised onto millimeter-scale substrates, i.e., beads or Raschig rings [108], to be used as the 3D electrode, as in the design of Liu et al [106] shown in Figure 26. Their system used Fe2O3/graphite and TiO2-coated glass beads as the 3D electrode.…”
Section: Three-dimensional Electrode Reactormentioning
confidence: 99%
See 1 more Smart Citation
“…Post-treatment filtration is still required to separate the photocatalyst from the solution, and cost/energy analysis also needs to be performed to examine if the additional complexity and input energy are worth the increased efficiency. To remove the need for filtration, the photocatalyst can be immobilised onto millimeter-scale substrates, i.e., beads or Raschig rings [108], to be used as the 3D electrode, as in the design of Liu et al [106] shown in Figure 26. Their system used Fe2O3/graphite and TiO2-coated glass beads as the 3D electrode.…”
Section: Three-dimensional Electrode Reactormentioning
confidence: 99%
“…The inclusion of the 3D electrode improved the rate of berberine chloride form degradation, and a rate constant (k) of 0.015 min −1 was achieved with the 3D electrode under irradiation, compared to k = 0.007 min −1 without irradiation and k = 0.001 min −1 without irradiation and the 3D electrode. The efficiency analysis shows that the 3D electrode had a higher mineralisation To remove the need for filtration, the photocatalyst can be immobilised onto millimeterscale substrates, i.e., beads or Raschig rings [108], to be used as the 3D electrode, as in the design of Liu et al [106] shown in Figure 26.…”
Section: Three-dimensional Electrode Reactormentioning
confidence: 99%
“…Previous literature has mainly focused on oxidizing various contaminants in rainwater purification using PC (Ab Aziz et al 2018;Nwoke et al 2018;Waso et al 2020). However, only a few studies have been carried out using PEC for rainwater treatment.…”
Section: Vbmentioning
confidence: 99%
“…[19,20] The photoactivated strategies such as photodynamic therapy, photothermal therapy or photocatalysis could also possess antimicrobial ability. [21] Especially, the photocatalysis could combat the bacterial through the ROS including hydroxyl radical (•OH) and superoxide radical (O 2 •−…”
Section: Doi: 101002/smll202103348mentioning
confidence: 99%